Measuring General Health Literacy in Chinese adults: validation of the HLS19-Q12 instrument - Rongmei Liu; Qiuping Zhao; Mingyang Yu; Hui Chen; Xiaomo Yang; Shuaibin Liu; Orkan Okan; Xinghan Chen; Yuhan Xing; Shuaijun Guo (BMC Public Health, 2024)
Abstract Background Health literacy measurement lays a solid foundation to identify associations with health outcomes and monitor population health literacy levels over time. In mainland China, most existing health literacy instruments are either knowledge-based or practice-based, making health literacy results incomparable between China and other countries. This study aimed to examine the reliability and validity of the 12-item Health Literacy Population Survey (HLS19-Q12) in a general population of Chinese adults. Methods A cross-sectional study was conducted to recruit primary carers of students from 11 schools in Zhengzhou, Henan Province, using convenience cluster sampling. Participants completed an online self-administered survey that collected information on key sociodemographics, health literacy (HLS19-Q12 and a comparison tool: Health Literacy Questionnaire (HLQ)), and health-related outcomes. Using the COnsensus-based Standards for the selection of health status Measurement Instruments (COSMIN) checklist as a guideline, we tested internal consistency, test-retest reliability, content validity, structural validity, concurrent predictive validity, and convergent validity of the HLS19-Q12. Results Overall, 14,184 participants completed the full survey. The HLS19-Q12 showed excellent internal consistency (Cronbach’s α = 0.93), moderate test-retest reliability (intra-class correlation coefficient = 0.54), satisfactory content validity (based on the 12-matrix health literacy model), and strong structural validity (comparative fit index = 0.94, Tucker and Lewis’s index of fit = 0.93, root mean square error of approximation = 0.095). Concurrent predictive validity results showed health literacy was associated with both health determinants and health-related outcomes. The HLS19-Q12 had weak to strong correlations (coefficients = 0.24 to 0.42) with the nine scales of the HLQ. Respondents had an average score of 81.6 (± 23.0) when using the HLS19-Q12, with 35.0% and 7.5% having problematic and inadequate levels of health literacy, respectively. Conclusions The HLS19-Q12 is a reliable and valid instrument to measure health literacy in our sample. Further validation is needed with a more nationally representative sample of Chinese adults. The HLS19-Q12 could be used as a comprehensive, skills-based, and easy-to-administer health literacy assessment tool integrated into population surveys and intervention evaluations.